Synchronizing Poverty Alleviation Strategy: Lesson Learned from Central Java, Indonesia - Yudhistira, Indra; Prawata Hadi, Sudharto; Prabawani, Bulan (JURNAL ILMU SOSIAL, 2023)
Budget constraints and the impact of the COVID-19 pandemic are limiting poverty alleviation initiatives in Central Java. Local governments in Central Java are attempting to refocus priority policies by collaborating with local government agencies and CSR participants in order to reduce poverty, which necessitates the convergence of social protection contributions and CSR contributions as a solution that needs to be optimized in Central Java. One of the poverty alleviation program's action steps is to maximize the e-government CSR reporting system known as SILAP CSR and the CSR forum working group at the Central Java Province level to facilitate the convergence of social protection contributions based on potential, problems and needs in communities. However, SILAP CSR and the CSR forum working group have not been adequately exploited and socialized to the 35 regency and city governments across Central Java, hurting the quality and number of CSR participants in the local area. As a result, this study was carried out to determine the extent to which SILAP CSR and the CSR Forum working group synchronized their performance in poverty alleviation efforts among government agencies and CSR players at the Central Java Province level. This study employs qualitative methods, including in-depth interviews and Nvivo, to examine the impact and evaluation of SILAP CSR and the CSR forum working group at the Central Java Province level, based on the theoretical foundations of stakeholders, governance, and leadership as essential keys to maximizing poverty alleviation strategies through internal and external collaboration. The findings indicate that SILAP CSR and the CSR forum working group at the Central Java Provincial level are not in sync with the 35 regencies and city administrations in Central Java. As such, different techniques are required to improve their performance: 1) internal collaboration among government agencies and partnerships with CSR participants to reduce technical and ego-sectoral barriers; 2) building sustainable participation through MUSRENBANG and CSR forum working group; 3) updating SILAP CSR data and synchronizing with various e-government and open data sources inclusively; 4) continuous supervision to avoid potential duplication and the risk of greenwashing CSR participants; and 5) the role of autocratic transformational leadership.